Girolamo Camerata and the Querelle des Femmes between Discourse and Paradox - Bakić, Jelena (Renaissance and Reformation / Renaissance et Réforme, 2023)
In this article, I focus on the rhetoric of the querelle des femmes in the only book by Girolamo Camerata, Trattato dell’honor vero, et del vero dishonore (1567), offering a critical analysis of the chapter entitled “Questione dove si tratta chi più meriti honore o la donna, o l’huomo di M. Girolamo Camerata da Randazzo, Siciliano Dottor dell’Arti” (Question where it is discussed who merits more honour, woman or man, by Girolamo Camerata of Randazo, Sicilian Doctor of Arts). The main aim is to show how Camerata, in line with the prevalent rhetoric of the time and the other authors of the querelle des femmes, relies on androcentric literary codes (rhetoric within the androcentric cultural environment) and socially and culturally prescribed gender roles in order to provide reasons why women should be considered worthier of honour and more perfect than men. His work is an example of how arguments once used in reproach can paradoxically be reversed and serve the opposite aim (e.g., when the humoral theory is invoked to show that women are cold and therefore inferior, and then later to show that they are hot and therefore superior). Similarly, arguments citing bodily weakness as proof of mental inferiority can easily be turned to women’s advantage, connecting the body’s tenderness with greater mental activity.